2017
DOI: 10.1155/2017/2729807
|View full text |Cite
|
Sign up to set email alerts
|

UTE-T2Analysis of Diseased and Healthy Achilles Tendons and Correlation with Clinical Score: An In Vivo Preliminary Study

Abstract: Objective. To compare T2⁎ value of healthy and diseased Achilles tendons (AT) with a recently introduced three-dimensional ultrashort echo time (3D-UTE) sequence and analyze the correlation between T2⁎ value and clinical scores. Methods. Ten patients with symptomatic Achilles tendon and ten healthy volunteers were investigated with 3D-UTE sequence on a 3T magnetic resonance (MR) scanner. T2⁎ values of four regions in Achilles tendons were calculated. The clinical outcomes of patients were evaluated according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Therefore, specialized ultrashort echo time MRI techniques have been developed to effectively capture these rapidly decaying signals and allow for quantitative evaluation of T2*. 13,14,18,24,43,55,63,66,82,85,88 Previous studies have established good correlations between T2* values, histopathology, microscopy, and biomechanical testing. 38,50,72 As with T2 metrics, numerous studies have demonstrated that prolonged T2* values are indicative of the presence and severity of tissue pathology.…”
Section: T2* Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, specialized ultrashort echo time MRI techniques have been developed to effectively capture these rapidly decaying signals and allow for quantitative evaluation of T2*. 13,14,18,24,43,55,63,66,82,85,88 Previous studies have established good correlations between T2* values, histopathology, microscopy, and biomechanical testing. 38,50,72 As with T2 metrics, numerous studies have demonstrated that prolonged T2* values are indicative of the presence and severity of tissue pathology.…”
Section: T2* Mappingmentioning
confidence: 99%
“…82 As degenerative changes often precede tendon rupture, evaluation of T2* values has also proven useful for the evaluation of tendinosis. 14,34,63 Future applications of these techniques will be directed to correlating MRI assessment of collagen orientation to material properties, such as the patellar tendon in elite basketball players, 4 as T2* values are also affected by direct tissue loads. 37 Such quantitative assessments, like shear wave sonoelastography, may provide an objective noninvasive assessment of the ability of tissues such as tendons and ligaments to withstand repetitive loads, which has implications with regard to athletic performance and return to play.…”
Section: T2* Mappingmentioning
confidence: 99%
“…Ultrashort echo time (UTE) based MRI methods have been used to capture average T2 * relaxation time of the Achilles tendon (mid-portion, insertion region, muscle-tendon junction, and whole Achilles tendon-aponeurosis) in a group of recreational long distance runners compared to healthy volunteers, showing longer T2 * relaxation times in the mid-portion and whole Achilles tendon-aponeurosis for runners ( Grosse et al, 2015 ). Longer T2 * relaxation times are believed to reflect a greater amount of free water protons between collagen fibres, reduced collagen alignment, and have previously been reported to distinguish between healthy and pathological Achilles tendons ( Juras et al, 2012 , 2013 ; Gärdin et al, 2016 ; Qiao et al, 2017 ). However, it remains unclear if T2 * relaxation time, which is indicative of collagen organisation/disorganisation ( Juras et al, 2013 ; Gärdin et al, 2016 ), is related to Young’s modulus in the free Achilles tendon.…”
Section: Introductionmentioning
confidence: 99%
“…Recent development in ultrashort echo time (UTE) imaging techniques has enabled MRI to detect signal from tissues with short T 2 *, such as cortical bone, tendons, and ligaments. Many preclinical UTE studies have been conducted in the field of musculoskeletal (MSK) imaging and have shown that the resolved UTE signal can help to directly image the morphology of certain short T 2 * tissues and to detect lesions . In addition, it has been reported that the UTE signal allows for more reliable multi‐component T 2 * fitting to better characterize lesions quantitatively in the short T 2 * tissues …”
Section: Introductionmentioning
confidence: 99%